PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA KONSEP PERMASALAHAN LINGKUNGAN HIDUP DAN PENANGGULANGANNYA MATA PELAJARAN IPS TERPADU KELAS VIIIB DI SMP NEGERI 2 ANGSANA TAHUN PELAJARAN 2014-2015 - Rabiatu Adawiyah (Universitas Lambung Mangkurat, 2016)
The aim of this research is to reveal the implication of guided inquiry learning in improving the VIIIB of SMP Negeri 2 Angsana students activities and learning outcomes and learning Integrated Social Science on concepts of the environment problem and the solution to VIIIB of SMP Negeri 2 Angsana in the year of 2014-2015. This classroom action research was conducted in two cycles. Every cycle consisted of two meetings. The qualitative data were analyzed descriptively, whereas the quantitative data were analyzed in the form of percentage.The result of this research showed that there were 23 students (71,87%) who reached the standard score in the first cycle, and 29 students (90,63%) who reached the standard score in the second cycle. It can be concluded that the implication of guided inquiry learning can improve the activities, learning outcomes, and positive responses of the VIIIB students of SMP Negeri 2 Angsana, Tanah Bumbu Regency in learning Integrated Social Science. Furthermore, it is suggested for teachers to make fixed regulations towards the teaching process, and give rewards to the students with highest scores. Basides, since the studentsunderstandings are fifferent, so it is suggested for the teachers to explain the materials clearly and not too fast so that the students can reach the standard score and their responses become positive.Key words: Guided inquiry learning, Learning activity, Study result Umumnya, proses belajar mengajar Ilmu Sosial Terpadu di SMP Negeri 2 Angsana Kabupaten Tanah Bumbu masih monoton dan konvensional. Kondisi ini membuat siswa tidak termotivasi dalam belajar IPS. Akibatnya, kegiatan belajar siswa dan hasil belajar adalah tujuan memuaskan. penelitian ini mengungkapkan implikasi dari inkuiri terbimbing pembelajaran dalam meningkatkan kegiatan siswa VIIIB SMP Negeri 2 Angsana. Penelitian ini menggunakan penelitian tindakan kelas yang dilakukan dalam dua siklus. Setiap siklus terdiri dari dua pertemuan. Data kualitatif dianalisis secara deskriptif, sedangkan data kuantitatif dianalisis dalam bentuk persentase. Hasil penelitian ini menunjukkan bahwa ada 23 siswa (71,87%) yang mencapai skor standar dalam siklus pertama, dan 29 siswa (90,63%) yang mencapai skor standar dalam siklus kedua. Dapat disimpulkan bahwa implikasi pembelajaran inquiri dapat meningkatkan aktivitas, hasil, dan tanggapan positif dari siswa VIIIB SMP Negeri 2 Angsana, Kabupaten Tanah Bumbu dalam belajar IPS Terpadu belajar. Selain itu, disarankan bagi guru untuk membuat peraturan tetap terhadap proses mengajar, dan memberikan penghargaan kepada siswa dengan nilai tertinggi.Kata kunci:Pembelajaran inkuiri terbimbing, kegiatan Belajar, hasil studi